REINTERPRETING ISLAMIC HERITAGE IN CONTEMPORARY CIVILIZATIONAL CONTEXTS - Miftahul Ilmi Fadhilaturrahman (Senarai: Journal of Islamic Heritage and Civilization, 2026)
This editorial introduces Volume 2, Number 2 (2026) of Senarai: Journal of Islamic Heritage and Civilization, which brings together eight original research articles examining Islamic heritage as a dynamic and evolving civilizational process. Addressing a wide range of themes, from contemporary Qur’anic interpretation, family law and gender justice, Islamic legal ethics, and economic practices to historical encounters and vernacular architecture, this issue highlights the ongoing interaction between normative Islamic values and changing social realities. Rather than approaching Islamic heritage as a static legacy of the past, the contributions in this volume emphasize reinterpretation, dialogue, and contextual engagement as central to the vitality of Islamic civilization. Collectively, the articles demonstrate that Islamic civilization develops through critical reflection and openness to interdisciplinary perspectives. This volume affirms Senarai’s commitment to fostering reflective, inclusive, and ethically grounded scholarship that situates Islamic heritage within broader civilizational debates and contemporary global challenges.